PERKEMBANGAN KINERJA KEUANGAN PT. INDOFOOD SUKSES MAMKMUR TBK PADA PERIODE 2012-2016 - Syabani Sasongko Aji (JURNAL EKOBIS DEWANTARA, 2018)
Abstract Company Performance is the achievement of the company in that period. Performance measurement is used by companies to make improvements to their operational activities in order to compete with other companies. The company’s ability to generate profits is the key to the company’s success to be said to have good corporate performance. To assess the company’s activities in a certain period of time to interested parties and one of the factors that can show how the company’s performance is good or not, namely with the analysis of financial statements. The technique used in this research is documentation technique, is a source of data obtained by researchers indirectly, through intermediary media. The results of this study indicate that the development of financial performance can be measured by analysis of financial statements or financial ratios. Keywords : current ratio, return on equity, total asset turnover, inventory turnover, debt to equity ratio, profit margin, znd economic profitability.